2016
DOI: 10.1002/ejic.201501100
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of Isoelectronic Ruthenium Nitrosyl and Diazonium Complexes in Frozen PVC Matrices: Retention of Dinitrogen on Ruthenium Following Photochemical Phenyl Radical Loss

Abstract: 2 , has previously been shown to result in generation of the phenyl radical, presumably through decomposition a photogenerated diazenyl radical. Examination of this photolysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It has been reported that the S atom easily coordinates with the Cu ( Scheme 5 ) [ 28 , 29 , 30 ]. The coordination of DMSO with intermediate A resulted in the formation of intermediate B ([ B − I] + , m/z = 332.0387, please see Supplementary Materials Figure S4 ) [ 31 , 32 ]. It should be noted that in this step we only considered DMSO as a neutral nucleophile.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the S atom easily coordinates with the Cu ( Scheme 5 ) [ 28 , 29 , 30 ]. The coordination of DMSO with intermediate A resulted in the formation of intermediate B ([ B − I] + , m/z = 332.0387, please see Supplementary Materials Figure S4 ) [ 31 , 32 ]. It should be noted that in this step we only considered DMSO as a neutral nucleophile.…”
Section: Resultsmentioning
confidence: 99%
“…Alongside their interest in the understanding of important biological processes implicating nitric oxide [3], these molecules possess the potential for efficient optical data storage based on long-lived metastable states (MS) [15,16].…”
Section: Introductionmentioning
confidence: 99%